Determinants of Capital Structure of UK Companies - Huang, Xu (2013)
This paper aims to examine the determinants of capital structure of the UK companies and to provide some up-to-date empirical evidence for previous literatures. The sample of this study involves all non-financial companies listed on the FTSE350 Index during the time period from 2003 to 2012. The analysis of variance and panel data regression models are performed to test what factors may affect the UK companies’ financing decisions. In each model, three different measures of financial leverage are adopted, i.e. total leverage, long-term leverage and short-term leverage. Eight potential determinants of capital structure, including firm size, growth opportunity, profitability, tangibility, non-debt tax shield, liquidity, uniqueness and industry classification are used in this paper. Overall, the results suggest that firm size, tangibility, liquidity, non-debt tax shield and industry classification are strongly correlated with capital structure in the manner suggested by theories. The negative relationships between size and leverage as well as between liquidity and leverage confirm the prediction of pecking order theory, while the findings about the effects of tangibility and non-debt tax shield on debt levels are in favour of trade-off theory and agency cost theory. However, the result for uniqueness is inconsistent with previous empirical evidence that a strong inverse relationship exists between uniqueness and leverage ratios. After running the regression for each industry, profitability becomes a vital determinant of financial decisions for many industries, whereas growth opportunity is still insignificant and has not enough explanatory power on the financing choices of the UK companies.